Study of the operating parameters of fuel equipment units of MTZ-80x tractors in natural and climatic conditions of the republic of Uzbekistan - Mirzaev Ilhomjon; Zulunov Zukhridin; Abdimominov Ikromjon; Yasharov Madiyorbek (E3S Web of Conferences)
The climate of the Republic of Uzbekistan is dry, sharply continental, which in the conditions of agricultural production has a significant impact on the contamination of diesel fuel in tractor tanks and the reliability of the fuel system as a whole. In connection with which studies were conducted on the operating parameters of the fuel equipment units of MTZ-80X tractors operated in the natural and climatic conditions of the Republic of Uzbekistan. The results of the research will be applied in further research and will be aimed at adjusting the standards for the service life of air and fuel filters and the performance of maintenance operations for tractors operating in the natural and climatic conditions of the Republic of Uzbekistan.